DOI: 10.2298/bg20130226pljevljakusic
|View full text |Cite
|
Sign up to set email alerts
|

Influence of growing conditions on morphological and chemical properties and biological effects of extracts of Arnica montana L.

Abstract: Belgrade, 2012(1,7 -2,4%).Mikroskopskim snimanjem samlevenog biljnog materijala pod različitim uveličanjima ustanovljena je jednostavna procedura identifikacije cveta arnike u odnosu na dva pretpostavljena falsifikata. Tako Since the A. montana plant specie is not native to the region of Serbia, although it occurs spontaneously in some mountain areas of neighboring countries and the Balkans in general, the aim of this study was to find a suitable technology solution of field cultivation based on the examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0
1

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 63 publications
3
3
0
1
Order By: Relevance
“…In this study, the content of STLs in accessions with Bulgarian provenance agreed with that reported for Arnica by Pljevljakušić, 2014 (from 4.6 mg/g to 13.9 mg/g),[ 23 ] and was intermediate between the values reported by Heldmaier, 2007 (0.64%)[ 32 ] and Clauser et al . 2012 (up to 2.31%).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this study, the content of STLs in accessions with Bulgarian provenance agreed with that reported for Arnica by Pljevljakušić, 2014 (from 4.6 mg/g to 13.9 mg/g),[ 23 ] and was intermediate between the values reported by Heldmaier, 2007 (0.64%)[ 32 ] and Clauser et al . 2012 (up to 2.31%).…”
Section: Discussionsupporting
confidence: 90%
“…[ 29 ] On the other hand, chlorogenic acid was up to 3 orders of magnitude lower than that established by Albert et al ., 2009 (4.4–6.7 mg/g)[ 12 ] and Pljevljakušić, 2012 (1.9–6.57 mg/g). [ 23 ] The content of caffeic acid was in agreement with the literature. [ 15 29 ] The difference could be due to the methods of sample preparation and quantification used as well as the number and variety of phenolic acids included in the amounts stated.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The genus has more than 30 different species, and they differ significantly in the content of medicinal components, with A. montana being the species used most widely for its medicinal value ( Kowalski et al, 2015 ; Kriplani et al, 2017 ) and the flower heads being the part of the plant containing the highest levels of biologically active compounds ( Galambosi, 2004 ; Ganzera et al, 2008 ; Spitaler et al, 2008 ). The antimicrobial activity of the plant extracts has been studied extensively, as they have been shown to possess antimicrobial activity against a wide range of microorganisms ( Brantner and Grein, 1994 ; Koo et al, 2000 ; Klaas et al, 2002 ; Iauk et al, 2003 ; Pljevljakušić, 2013 ; Bulfon et al, 2014 ; Kryvtsova, 2020 ). The anticancer activity of various components of A. montana has been investigated thoroughly, particularly sesquiterpene lactones, the main active compound of the plant ( Lee et al, 1972 ; Lyß et al, 1998 ; Willuhn, 1998 ; Douglas et al, 2004 ; Huang P.-R. et al, 2005 ; Ghantous et al, 2010 ; Chaturvedi, 2011 ; Lim et al, 2012 ; Chadwick et al, 2013 ; Jakobs et al, 2016 ; Drogosz and Janecka, 2019 ; Kriplani and Guarve, 2020 ).…”
Section: Introductionmentioning
confidence: 99%